Evaluation of lower extremity overuse injury potential in runners - Hreljac, A.; Marshall, R. N.; Hume, P. A. (Medicine & Science in Sports & Exercise, 2000)
. Introduction: The purpose of this study was to identify biomechanical and anthropometric variables that contribute to overuse injuries in runners. Methods: Comparisons were made between a group of runners who had sustained at least one overuse running injury and a group of runners who had been injury free throughout their running careers. Groups were well matched in important training variables. Synchronized kinetic and rearfoot kinematic variables of both feet were collected by filming subjects running over a force platform at a speed of 4 m·s-1. Results: The injury-free group demonstrated significantly greater posterior thigh (hamstring) flexibility, as measured by a standard sit and reach test. This was the only anthropometric variable in which the groups differed. Within each group, there were no significant differences between left and right foot landing for any biomechanical variable. Biomechanical variables that demonstrated significantly lower values for the injury free group were the vertical force impact peak and the maximal vertical loading rate, with the maximal rate of rearfoot pronation and the touchdown supination angle showing a trend toward being greater in the injury free group. Conclusion: These results suggest that runners who have developed stride patterns that incorporate relatively low levels of impact forces, and a moderately rapid rate of pronation are at a reduced risk of incurring overuse running injuries.